2001
DOI: 10.1177/0018726701548004
|View full text |Cite
|
Sign up to set email alerts
|

Employee Involvement Management Practices, Work Stress, and Depression in Employees of a Human Services Residential Care Facility

Abstract: This article tests a theoretically driven model of the relationship between work environment, specifically, management practices, and employee mental health, specifically depression. It draws on theoretical perspectives connecting work environment and stress, and on others linking stress and depression. It also examines sense of coherence as a possible mediator of the relationships among work environment, work stress, and depression. Results showed that perceived exposure to employee involvement management pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
73
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 55 publications
8
73
0
8
Order By: Relevance
“…However, most Brazilian judges are constantly overloaded, considering the number of cases they need to resolve (CNJ, 2015). Studies from occupational psychology have shown that stimuli that cause stress at work reinforce workers' negative emotions (Mackie, Holahan, & Gottlieb, 2001). Thus, when demands and the workload on the professional are excessive, negative emotions tend to intensify (Jex, 1998;Paschoal, Torres, & Porto, 2010).…”
Section: Court Caseload and Judicial Performancementioning
confidence: 99%
“…However, most Brazilian judges are constantly overloaded, considering the number of cases they need to resolve (CNJ, 2015). Studies from occupational psychology have shown that stimuli that cause stress at work reinforce workers' negative emotions (Mackie, Holahan, & Gottlieb, 2001). Thus, when demands and the workload on the professional are excessive, negative emotions tend to intensify (Jex, 1998;Paschoal, Torres, & Porto, 2010).…”
Section: Court Caseload and Judicial Performancementioning
confidence: 99%
“…These include practices that Employee involvement can be used as a measure of job control, since high involvement practices give workers greater control over their jobs (Boxall & Macky, 2014;Mackie et al, 2001;Macky & Boxall, 2008;Wood, 2008). Researchers argue that involvement practices can reduce work stress through an increased sense of personal control, less role ambiguity, increasing participation in decision-making and by providing for greater utilization of skills.…”
Section: Employee Involvement and Job Satisfactionmentioning
confidence: 99%
“…Several studies demonstrate that employees who are involved in decision-making processes tend to feel a heightened sense of ownership over their job performance because they feel personally responsible for how tasks are accomplished (Mackie et al, 2001;Wood et al, 2012). Furthermore, Warr (2007) suggests that greater employee involvement may increase the meaningfulness of work, such that individuals consider their work as a career rather than simply as a job, this in turn may increase their job satisfaction.…”
Section: Employee Involvement and Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations